180 Recovery Trajectories and Long-Term Outcomes in Traumatic Brain Injury: A Secondary Analysis of the Phase 3 COBRIT Clinical Trial. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Puffer, Ross; Yue, John K; Billigen, Julia; Sharpless, Jane; Fetzick, Anita L; Puccio, Ava; Diaz-Arrastia, Ramon; Okonkwo, David O
Abstract: INTRODUCTION: Prospects for recovery after traumatic brain injury (TBI) are often underestimated, and this can lead to withdrawal of care in the severe TBI patient in a coma who may ultimately have a favorable outcome with continued aggressive care. METHODS: A secondary analysis of the phase 3 COBRIT was performed analyzing recovery trajectories and long-term outcomes at 30, 90, and 180 d after injury. Subjects were analyzed according to their Glasgow Coma Scale at presentation, and outcomes were based on GOS-E. A GOS-E of 4 or greater was considered favorable. RESULTS: There were high rates of favorable outcome (63% of severe TBI, 87% of moderate TBI, and 96% of complicated mild TBI) at 6-mo follow-up. These favorable outcomes often converted from initially low rates of favorable outcome at 1-m follow-up (21% in severe TBI, 54% in moderate TBI, and 87% in complicated mild TBI). Recovery trajectory projections suggest that further improvement is likely seen beyond 6 mo after injury, and the long-term outcomes in moderate and severe TBI more closely mimic recovery in complicated mild TBI when projected to follow-up at 2 yr after injury. CONCLUSION: The majority of patients had favorable outcomes by GOS-E at 6 mo after injury in all TBI groups (complicated mild 96%, moderate 87%, severe 63%). There was substantial improvement in all groups from 1-mo to 6 mo after injury, and predictive models suggest that this improvement continues beyond 6 mo. The small group of subjects with an unfavorable outcome (GOS-E 2-3) at 1 mo should continue close observation as approximately 20% will improve to a favorable outcome by 6 mo after injury. Further clinical trials should evaluate outcomes beyond 6 mo to better capture recovery trajectories and assist providers with more accurate predictions for individual patients. Future clinical trials should also consider recovery curves with repeated measures to assess outcomes, as arbitrary single-moment outcome determination likely underestimates treatment effect in TBI care.